Lateral instability in normal viscous fingers. - Ledesma-Aguilar, R; Quevedo-Reyes, M; Corvera Poiré, E; Hernández-Machado, A (2005)
We study a low-amplitude, long-wavelength lateral instability of the Saffman-Taylor finger by means of a phase-field model. We observe such an instability in two situations in which small dynamic perturbations are overimposed to a constant pressure drop. We first study the case in which the perturbation consists of a single oscillatory mode and then a case in which the perturbation consists of temporal noise. In both cases the instability undergoes a process of selection.